Lessons From Becoming a Data-Driven Organization - Kiron, David (MIT Sloan Management Review, 2016)
Organizations across the business spectrum are awakening to the transformative power of data and analytics. They are also coming to grips with the daunting difficulty of the task that lies before them. It's tough enough for many organizations to catalog and categorize the data at their disposal and devise the rules and processes for using it. It's even tougher to translate that data into tangible value. But it's not impossible, and many organizations, in both the private and public sectors, are learning how.